SWOT Analysis of Islamic Education Development Strategy for "Muallaf Center Indonesia Peduli" North Sumatera Region - Arie Bastian Hadinata; Asmuliadi Lubis; Tika Dewi (TADRIS: Jurnal Pendidikan Islam, 2023)
Muallaf is a person who converts to Islam from another religion. Muallaf needs good Islamic education guidance to be able to understand and practice the teachings of Islam correctly. Muallaf Centre Indonesia Peduli (MCIP) is an organization that works in the field of muallaf guidance, especially in North Sumatra. This article aims to analyze the strategy of Islamic education guidance carried out by MCIP Regional North Sumatra by using the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats). This article uses a qualitative approach and collects data through observation, interviews, and documentation. The results show that MCIP Regional North Sumatra has several strengths, weaknesses, opportunities, and threats in its guidance strategy. The strengths include having a clear vision and mission, a structured curriculum and learning module, adequate facilities and infrastructure, competent and experienced teachers, cooperation with related parties, and support from the Muslim community. The weaknesses include the lack of professional human resources, the lack of budget and operational funds, the lack of monitoring and evaluation of the process and results of guidance. We hope that this article can become a concrete recommendation for practical implementation of the strategy for developing Islamic education. Meanwhile, MCIP can involve collaboration with related parties, increasing human resources, developing a more responsive curriculum and promotional strategies to increase visibility organization.